1999
DOI: 10.1200/jco.1999.17.8.2429
|View full text |Cite
|
Sign up to set email alerts
|

Medullary-Type Poorly Differentiated Adenocarcinoma of the Large Bowel: A Distinct Clinicopathologic Entity Characterized by Microsatellite Instability and Improved Survival

Abstract: All these data strongly indicate that MTAs represent a distinct pathologic entity, with specific histologic appearance and peculiar clinical and genetic features. These tumors need to be classified separately from other poorly differentiated colorectal carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
85
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 39 publications
5
85
1
2
Order By: Relevance
“…This result is in accord with that of other investigators. 4,10,14 Although the high incidence of absent hMLH1 expression was reported in poorly differentiated colorectal adenocarcinomas, 14 our results indicated that in poorly differentiated adenocarcinoma, the medullary-type carcinoma is primarily affected as compared with pleomorphictype carcinoma. In view of the histopathological type of tumor, we are the first to describe hypermethylation of the hMLH1 promoter in medullarytype carcinomas.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…This result is in accord with that of other investigators. 4,10,14 Although the high incidence of absent hMLH1 expression was reported in poorly differentiated colorectal adenocarcinomas, 14 our results indicated that in poorly differentiated adenocarcinoma, the medullary-type carcinoma is primarily affected as compared with pleomorphictype carcinoma. In view of the histopathological type of tumor, we are the first to describe hypermethylation of the hMLH1 promoter in medullarytype carcinomas.…”
Section: Discussionmentioning
confidence: 58%
“…21,31 These facts may contribute to the observation that medullary-type carcinomas occur more frequently in the older female patient and in the proximal colon. 6,10 The present study has suggested that medullarytype poorly differentiated carcinomas should be distinguished from other adenocarcinomas with minimal or no glandular differentiation due to its biological behavior. Since approximately 90% of medullary-type carcinomas showed an absence of hMLH1 protein expression together with microsatellite instability, immunohistochemistry for the detection of hMLH1 protein may be useful in predicting the tumor type.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations